Adipogenic differentiation of human mesenchymal stromal cells is down-regulated by microRNA-369-5p and up-regulated by microRNA-371 - Bork, Simone; Horn, Patrick; Castoldi, Mirco; Hellwig, Isabelle; Ho, Anthony Dick; Wagner, Wolfgang (Journal of cellular physiology, 2011)
Long-term culture of human mesenchymal stromal cells (MSC) has implications on their proliferation and differentiation potential and we have demonstrated that this is associated with up-regulation of the five microRNAs miR-29c, miR-369-5p, miR-371, miR-499, and let-7f. In this study, we examined the role of these senescence-associated microRNAs for cellular aging and differentiation of MSC. Proliferation was reduced upon transfection with miR-369-5p, miR-371, and miR-499. Adipogenic differentiation was impaired by miR-369-5p whereas it was highly increased by miR-371. This was accompanied by respective gene expression changes of some adipogenic key molecules (adiponectin and fatty acid-binding protein 4 [FABP4]). Furthermore luciferase reporter assay indicated that FABP4 is a direct target of miR-369-5p. Microarray analysis upon adipogenic or osteogenic differentiation revealed down-regulation of several microRNAs albeit miR-369-5p and miR-371 were not affected. Expression of the de novo DNA methyltransferases DNMT3A and DNMT3B was up-regulated by transfection of miR-371 whereas expression of DNMT3A was down-regulated by miR-369-5p. In summary, we identified miR-369-5p and miR-371 as antagonistic up-stream regulators of adipogenic differentiation and this might be indirectly mediated by epigenetic modifications. J. Cell. Physiol. 226: 2226-2234, 2011. © 2010 Wiley-Liss, Inc.
First published: 06 December 2010
Gesehen am 02.06.2022